Edith Stein, Philosopher. Life and Intellectual Trajectory - Viaña Rubio, Carlos Guillermo (2021)
The profound vital and intellectual unity of Edith Stein’s philosophical itinerary begins with a concept that permeates in her activity since the be ginning: philosophy understood as a rigorous science; it is then articulated around a theory of knowledge established during her phenomenological period and presupposed in her dialogue with the classical tradition; finally, it crystallizes in an anthropological ontology that had been the primary object of her philosophical vocation and that was performed between the purely phenomenological period and the encounter with the philosophia perennis. The aim of this article is to offer a summary introduction to his life and intellectual development by reviewing her work within the framework of the main milestones of her personal history.